Pausing of Chloroplast Ribosomes Is Induced by Multiple Features and Is Linked to the Assembly of Photosynthetic Complexes. Issue 3 (3rd January 2018) - Gawroński, Piotr; Jensen, Poul Erik; Karpiński, Stanisław; Leister, Dario; Scharff, Lars B.
Abstract : Ribosome pausing in chloroplasts is caused by multiple features of mRNA and nascent peptide chain and influences transmembrane protein folding and cofactor integration. Abstract: Many mRNAs contain pause sites that briefly interrupt the progress of translation. Specific features that induce ribosome pausing have been described; however, their individual contributions to pause-site formation, and the overall biological significance of ribosome pausing, remain largely unclear. We have taken advantage of the compact genome of chloroplasts to carry out a plastid genome-wide survey of pause sites, as a basis for studying the impact of pausing on posttranslational processes. Based on ribosomal profiling of Arabidopsis ( Arabidopsis thaliana ) chloroplast mRNAs, we demonstrate that a combination of factors—mRNA secondary structure, internal Shine-Dalgarno sequences, and positively charged amino acids in the nascent peptide chain—explains 95% of the major pause sites on plastid mRNAs, whereas codon usage has little impact. The distribution of the pause sites is nonrandom and conforms to distinct patterns in the vicinity of sequences coding for transmembrane domains, which depend on their orientation within the membrane as well as being next to sequences coding for cofactor binding sites. We found strong indications that the mechanisms causing ribosomal pausing and at least some of the ribosomes pause sites are conserved between distantly related plant species. In addition, the positions of features that cause pausing are well conserved in photoautotrophic plants, but less so in their nonphotosynthetic, parasitic relatives, implying that the synthesis and assembly of photosynthetic multiprotein complexes requires localized ribosome pausing.